Low-level mosaic trisomy 21 at amniocentesis in a pregnancy associated with a negative NIPT result, cytogenetic discrepancy in various tissues, perinatal progressive decrease of the aneuploid cell line and a favorable fetal outcome - Chih-Ping Chen; Te-Yao Hsu; Schu-Rern Chern; Peih-Shan Wu; Fang-Tzu Wu; Yen-Ting Pan; Chen-Chi Lee; Wen-Lin Chen; Wayseen Wang (Elsevier, 2023)
Objective: We present low-level mosaic trisomy 21 at amniocentesis associated with a favorable fetal outcome. Case report: A 31-year-old primigravid woman underwent non-invasive prenatal testing (NIPT) at 12 weeks of gestation, and the result was normal. She underwent amniocentesis at 16 weeks of gestation because of fetal choroid plexus cyst, and the result was 47,XX,+21[5]/46,XX[32]. Repeat amniocentesis was performed at 19 weeks of gestation, and the result was 47,XX,+21[5]/46,XX[15]. Simultaneous array comparative genomic hybridization (aCGH) analysis on uncultured amniocytes revealed the result of arr (21) × 3 [0.10], consistent with 10% mosaicism for trisomy 21. Prenatal ultrasound findings were unremarkable. She was referred for genetic counseling at 22 weeks of gestation, and the third amniocentesis was performed at 25 weeks of gestation, and the result was 46,XX (20/20 colonies). The parental karyotypes were normal. Simultaneous quantitative fluorescence polymerase chain reaction (QF-PCR) analysis on the DNA extracted from uncultured amniocytes and parental bloods excluded uniparental disomy (UPD) 21. aCGH analysis on uncultured amniocytes revealed arr 21q11.2q22.3 × 2.1 (log2 ratio = 0.1), consistent with 10-15% mosaicism for trisomy 21. Fluorescence in situ hybridization (FISH) analysis on uncultured amniocytes revealed 30% (30/100 cells) mosaicism for trisomy 21. The woman was advised to continue the pregnancy, and a phenotypically normal 2800-g female baby was delivered at 38 weeks of gestation. The karyotype of cord blood, umbilical cord and placenta were 47,XX,+21[1]/46,XX[39]. 47,XX,+21[4]/46,XX[36] and 46,XX (40/40 cells), respectively. When follow-up at age two months, the neonate was phenotypically normal. The peripheral blood had a karyotype of 47,XX,+21[1]/46,XX[39], and FISH analysis on buccal mucosal cells revealed 8.4% (7/83 cells) mosaicism for trisomy 21, compared with 0% in the normal control. Conclusion: Low-level mosaic trisomy 21 at amniocentesis can be associated with a negative NIPT result, cytogenetic discrepancy in various tissues, perinatal progressive decrease of the aneuploid cell line and a favorable fetal outcome.